Makna Sosial Budaya di Balik Praktik Perawatan Anak dan Pencegahan Stunting Pada Keluarga Balita di Wilayah Kerja Puskesmas Doda, Kabupaten Poso - Tange, Warni; Adam, Arlin; Alim, Andi (JURNAL BIDANG ILMU KESEHATAN, 2025)
Stunting is a chronic nutritional problem that impacts child growth and development and the quality of human resources. This study aims to explore the socio-cultural meanings behind childcare practices and stunting prevention among families of toddlers in the Doda Community Health Center (Puskesmas) working area, Lore Tengah District, Poso Regency. Using a qualitative descriptive approach, data were collected through in-depth interviews, observations, and documentation with families of toddlers experiencing stunting and supporting informants such as health cadres and community leaders. The results show that childcare practices are influenced not only by medical knowledge but also by cultural values, social structures, local norms, and beliefs that remain strong within the community. The role of mothers, grandmothers, and extended families is very dominant in caregiving, especially in limited economic contexts. While communities are beginning to adopt modern health approaches, traditional practices such as herbal remedies, dietary restrictions, and traditional parenting practices are still practiced. Understanding of stunting tends to be limited to the physical characteristics of short children, making culturally based health education crucial in supporting the transformation of parenting patterns. This study concludes that childcare and stunting prevention in the region are complex practices influenced by the interaction between local culture and the formal health care system. Culturally based and participatory interventions are needed to ensure health programs are more accepted and effective in sustainably reducing stunting rates.